Holistic Pedagogical Strategies: Combating Bullying in Islamic Secondary Schools Through Religious Education - Ummul Khaer; Mansur Mansur; Baso Syafaruddin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This study examines the strategies employed by Islamic Religious Education (PAI) teachers to prevent bullying at Islamic Secondary School 1 Poso, Poso Regency, Central Sulawesi Province, Indonesia. Bullying remains one of the most pressing problems in contemporary educational settings, generating substantial adverse consequences for students' mental health and social development. This study aimed to describe the forms of bullying occurring in the research site, identify their contributing factors, and analyze the strategies implemented by Islamic Religious Education teachers to prevent them. A qualitative descriptive-exploratory design was employed, combining pedagogical and psychological perspectives. Data were collected through direct observation, in-depth interviews with the head of madrasah, Islamic Religious Education teachers, guidance and counseling teachers, the vice-head for student affairs, and students, together with documentation studies, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that verbal bullying is the most prevalent form encountered, driven by family disharmony, the school environment, and social media exposure. The prevention strategies adopted by Islamic Religious Education teachers encompass sustained moral guidance and character coaching, the integration of Islamic values into classroom instruction, personalized approaches to students, cross-unit collaboration within the madrasah, and the application of educative rather than punitive sanctions. These findings underscore the strategic potential of religious education teachers as proactive psycho-spiritual agents of character transformation in mitigating bullying within Islamic secondary education.